2018
DOI: 10.1002/adsc.201800160
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Additions of Amines to Maleimides via Cooperative Catalysis

Abstract: A cooperative system comprising of a lithium Lewis acid and amine base significantly enhances the rate of the conjugate addition of a wide array of amines to maleimides. This operationally simple, scalable method provides mono‐addition products in high yields and purity. This conjugation was successfully applied to the kinase inhibitor crizotinib in a chemoselective ligation to create novel fluorescent probe.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…33 Similarly, Uno et al presented a system involving lithium as a Lewis acid and an amine base for the addition of a variety of amines to maleimides. 34 For the current research, we used the green chemistry approach presented by Vyborny et al We performed addition of tacrine molecule to maleimide (24) to obtain pyrrolidine-2,5-dione (31) in an 81% isolated yield (Scheme 3). A multistep synthetic procedure was adopted for the conjugate addition of substituted amines to maleimide (24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Similarly, Uno et al presented a system involving lithium as a Lewis acid and an amine base for the addition of a variety of amines to maleimides. 34 For the current research, we used the green chemistry approach presented by Vyborny et al We performed addition of tacrine molecule to maleimide (24) to obtain pyrrolidine-2,5-dione (31) in an 81% isolated yield (Scheme 3). A multistep synthetic procedure was adopted for the conjugate addition of substituted amines to maleimide (24).…”
Section: Resultsmentioning
confidence: 99%
“…Vybornyi et al reported the addition of heteronucleophiles (NH, SH, and OH) to N -Ar-substituted maleimides using optimized conditions of lithium perchlorate (LiClO 4 ) as a weak Lewis acid and water as a solvent at an elevated temperature (100 °C) . Similarly, Uno et al presented a system involving lithium as a Lewis acid and an amine base for the addition of a variety of amines to maleimides . For the current research, we used the green chemistry approach presented by Vyborny et al We performed addition of tacrine molecule to maleimide ( 24 ) to obtain pyrrolidine-2,5-dione ( 31 ) in an 81% isolated yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their reputation for exclusive thiol reactivity, maleimides are known to react with other nucleophiles, and especially amines. [63][64][65][66][67] also reacted to a small extent with both KF variants, suggesting a Cys-independent addition occurs at a low level for KF. These 5-F-Pci (38) conjugates cannot be detected or identified by mass spectrometry (MS), indicative of their vanishingly small quantities.…”
Section: Pyrocinchonimides Do Not Bioconjugate To Free Thiolsmentioning
confidence: 99%
“…2, and one that is di cult to attain by using conventional triggering methods, is that it enables generation of reactive functional groups (maleimide and furan) that can be used for further modi cation of the supramolecule. For example, maleimide moieties are well known to form covalent adducts with strong nucleophiles such as thiols and amines via a 1,4-Michael addition reaction 31,32 . Thus, the presence of maleimide functionality in the PDA might allow use of the PDA as a biothiol sensor.…”
Section: Introductionmentioning
confidence: 99%